Powder coating composition
Patent Information
- Application Number
- KR1020267027373
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-01-26
- Filing Date
- 2025-01-23
- Publication Date
- 2026-09-22
Smart Images

Figure PCT00001 
Figure PCT00002
Abstract
Description
Technology Field
[0001] Cross-reference regarding related applications
[0002] This application claims the benefit of priority to Japanese Patent Application No. 2024-009910 filed on January 26, 2024, the entire disclosure of which is incorporated herein by reference.
[0003] Technology field
[0004] The present invention relates to a high-temperature-melt fluororesin powder coating composition containing a filler that can be thickly coated by electrostatic powder coating. Background Technology
[0005] Fluoropolymers have excellent heat resistance, chemical resistance, electrical properties, and mechanical properties in addition to very low friction coefficients and non-stick characteristics, so they are widely used in all types of industrial fields such as chemical processing, mechanical devices, and electronic devices. In particular, high-temperature molten fluoropolymers exhibit fluidity at temperatures above their melting point, and thus can suppress the formation of pinholes when formed into a coating, so fluoropolymers can be used in coating compositions for fluoropolymer coatings.
[0006] Patent document 1 discloses an aqueous liquid coating of a fluororesin. Such liquid coatings are used as so-called slurry coatings having high concentration and high viscosity, allowing for thick coatings. However, slurry paints require a drying process, and there are concerns regarding environmental impacts due to the evaporation of the solvent.
[0007] On the other hand, high-temperature molten fluororesin powder coating has the advantage of enabling thick coatings without a volatile liquid medium, and the coating can be reused and does not generate VOCs (volatile organic compounds). As a method of powder coating using high-temperature molten fluororesin powder coating, electrostatic coating, in which the material to be coated and the powder coating are charged and coated, is generally used. Furthermore, when fillers are used to impart various properties to the high-temperature molten fluororesin powder coating, such as conductivity, wear resistance, and friction resistance, or to adjust appearance, such as color and gloss, the particles of the high-temperature molten fluororesin powder coating and the filler can be mixed together. However, dispersing filler particles within the high-temperature molten fluororesin powder particles is preferable in terms of thicker coatings, coating film durability, prevention of filler detachment from the coating film, and prevention of deviation within the coating film (see, for example, Patent Document 2).
[0008] In addition, to improve coating durability and corrosion resistance, enhance productivity, and reduce process costs, the coating must be able to be applied as a thick coat. The inventors have proposed a high-temperature molten fluororesin powder coating composition having a large film thickness that can be applied as a single thick coat and a large limit film thickness for overlapping coats (Patent Document 3). Patent Document 3 discloses a powder paint composition containing approximately 1% conductive filler based on the total composition by using high-temperature molten fluororesin particles containing a relatively small amount of conductive filler. However, the demand for corrosion resistance and conductivity of coating films is increasing year by year, and there is a need for coatings with further improved properties. Prior art literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2003-041126 Patent Document 2: Japanese Patent Publication No. H5-73147 Patent Document 3: Japanese Patent Application Publication No. 2022-127831
[0010] The object of the present invention is to provide a high-temperature-melt fluororesin powder coating composition containing a filler that, in addition to providing a thick coating, can produce a coating film having excellent corrosion resistance and surface properties.
[0011] [Means of Solving the Problem]
[0012] The present invention is a powder coating composition comprising a powder mixture comprising: a first high-temperature-melted fluororesin particle in which a filler is dispersed; a second high-temperature-melted fluororesin particle having an average particle diameter of 10 to 200 μm; and a charge modifier particle, wherein the amount of the filler is 7 to 15 weight% based on the total amount of the powder mixture.
[0013] In the powder coating composition of the present invention, the ratio of first high-temperature-melted fluororesin particles to second high-temperature-melted fluororesin particles is preferably 40 to 70:30 to 60 weight%, and the amount of charge modifier particles is preferably 0.01 weight% or more and 5 weight% or less with respect to the total amount of the powder coating composition. The average particle diameter of the second high-temperature-melted fluororesin particles is preferably larger than the average particle diameter of the first high-temperature-melted fluororesin particles. Furthermore, the filler is preferably a conductive filler, and the conductive filler is more preferably a carbon material having a graphene structure. Furthermore, the charge modifier particles are preferably graphite. Furthermore, the high-temperature-melted fluororesin is preferably a perfluororesin.
[0014] Another aspect of the present invention is a coating film prepared from a powder coating composition, and the film thickness is preferably 100 μm or more.
[0015] [Effect of the Invention]
[0016] The present invention provides a high-temperature-melt fluororesin powder coating composition containing a filler, which, in addition to being able to provide a thick coating, can produce a coating film having excellent corrosion resistance and surface properties. Specific details for implementing the invention
[0017] The powder coating composition of the present invention is a powder coating composition comprising (1) a first high-temperature-melted fluororesin particle, (2) a second high-temperature-melted fluororesin particle, and (3) a charge modifier particle.
[0018] (1) First high-temperature-melted fluororesin particle
[0019] The first high-temperature-melted fluororesin particles are described below. The first high-temperature-melted fluororesin particles of the present invention are particles in which a filler is dispersed in the high-temperature-melted fluororesin and are manufactured from the high-temperature-melted fluororesin and the filler.
[0020] The high-temperature-melt fluororesin used in the present invention may be suitably selected from resins known as high-temperature-melt fluororesins. Examples include polymers or copolymers of monomers selected from tetrafluoroethylene, chlorotrifluoroethylene, hexafluoropropylene, perfluoro(alkyl vinyl ether), vinylidene fluoride, and vinyl fluoride, copolymers of said monomers with ethylene, propylene, butylene, pentene, hexene, or other monomers having double bonds, or acetylene, propine, or other monomers having triple bonds, etc. Specific examples of high-temperature-melt fluororesins include low molecular weight high-temperature-melt polytetrafluoroethylene (high-temperature-melt PTFE), tetrafluoroethylene perfluoro(alkyl vinyl ether) copolymer (PFA), tetrafluoroethylene hexafluoropropylene copolymer (FEP), tetrafluoroethylene hexafluoropropylene perfluoro(alkyl vinyl ether) copolymer, tetrafluoroethylene ethylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, chlorotrifluoroethylene ethylene copolymer, etc.
[0021] Among these hot-melt fluororesins, perfluororesins such as hot-melt PTFE, PFA and FEP, tetrafluoroethylene, hexafluoropropylene, and perfluoro(alkyl vinyl ether) copolymers are particularly preferably used in terms of the non-stick properties and heat resistance of the coating film. Among these, PFA is preferred in terms of heat resistance. When PFA is used, the alkyl group of the perfluoro(alkyl vinyl ether) in PFA preferably has 1 to 5 carbon atoms, more preferably 1 to 3 carbon atoms. Furthermore, the amount of perfluoro(alkyl vinyl ether) in PFA is preferably in the range of 1 to 50 weight%.
[0022] Furthermore, the high-temperature melt fluororesin used in the present invention is preferably a high-temperature melt fluororesin having fluidity at temperatures above its melting point, in terms of favorable moldability during high-temperature melting. Specifically, the melt flow rate (MFR) of the high-temperature melt fluororesin is preferably 0.1 g / 10 min or more, more preferably 0.5 g / 10 min or more. Examples of resins include PFA, FEP, and tetrafluoroethylene, hexafluoropropylene, and perfluoro(alkyl vinyl ether) copolymers. PFA, which has a high melting point and excellent thermal fluidity, is particularly preferred. On the other hand, if the MFR is too high (if the melt viscosity is too low), appearance defects due to sagging or pulling during repeated coating and baking may easily occur, and the formation of a thick film becomes difficult, which is undesirable. Specifically, the MFR of the high-temperature melt fluororesin is preferably 30 g / 10 min or less, more preferably 25 g / 10 min or less, and particularly preferably 20 g / 10 min or less.
[0023] The high-temperature-melt fluororesin used in the present invention may be mixed with two or more high-temperature-melt fluororesins depending on the desired properties. Furthermore, non-high-temperature-melt polytetrafluoroethylene may also be included.
[0024] In the first high-temperature-melted fluororesin particle of the present invention, the filler is dispersed within the particle. In this specification, the filler material is preferably uniformly dispersed within the particle. Whether the filler is uniformly dispersed within the particle can be confirmed by determining whether the filler is uniformly dispersed when observing the surface of the particle with an electron microscope or the like. To manufacture resin particles by uniformly dispersing the filler in the high-temperature-melted fluororesin, for example, the method described in Patent Document 2 may be used.
[0025] Various types of fillers can be used as fillers dispersed within particles. Examples include metal powders, metal oxides (aluminum oxide, zinc oxide, tin oxide, titanium oxide, etc.), glass, ceramics, silicon carbide (SiC), silicon oxide, boron nitride, calcium fluoride, carbon black, graphite, mica, barium sulfate, and various resin particles. Fillers having various shapes, such as particle-shaped, fiber-shaped, or flake-shaped fillers, can be used as filler shapes.
[0026] In particular, the present invention is effective when using conductive fillers, examples of conductive fillers include metals, metal oxides (zinc oxide, tin oxide, titanium oxide, indium oxide, etc.), titanium carbide, titanium nitride, carbon fibers, carbon black, graphite, carbon nanotubes (CNT), and other carbon materials having a graphene structure, particles coated therewith, and composite particles. To achieve high conductivity, a combination of carbon black and carbon fibers is preferably used. Furthermore, in the present invention, materials having relatively low insulating properties, such as silicon carbide (SiC), specifically those with a volume resistivity of 10 8 Materials with a Ω·cm or lower value can also be used as conductive fillers. Silicon carbide (SiC) is preferably used to improve the wear resistance of the coating film.
[0027] Furthermore, when polar particles with hydrophilic surfaces, such as mica, aluminum oxide, boron nitride, and silicon oxide, are used, thick coating is difficult (it is thought that charge deviations occur during electrostatic coating because the electrical properties of the fluororesin and the filler differ), but such fillers can be used. Mica is preferably used because it can provide a glossy finish to the coating film.
[0028] Fillers having various shapes, such as particle-shaped, fiber-shaped, or flake-shaped fillers, can be used as particle shapes. The preferred mixing amount depends on the required characteristics, the type of filler, and the particle size, but is preferably 5 to 30 weight%, more preferably 10 to 25 weight%, and particularly preferably 15 to 20 weight%.
[0029] The average particle diameter of the first high-temperature-melted fluororesin particles is in the range of 2 to 100 μm, preferably 3 to 75 μm, more preferably 5 to 50 μm, and particularly preferably 8 to 35 μm. If the average particle diameter is small, not only is electrostatic powder coating difficult due to the influence of wind, but manufacturing is also difficult, and aggregation tends to occur during storage, causing defects. Furthermore, if the average particle diameter is too large, it is difficult to apply charge, and thus desorption tends to occur. Consequently, electrostatic coating becomes difficult, and the surface of the obtained coating film becomes rough.
[0030] Note that in this specification, “average particle diameter” refers to the particle diameter (d50) at the integral value of 50% of the particle diameter distribution obtained by laser diffraction / scattering.
[0031] (2) Second high-temperature molten fluororesin particles
[0032] The second high-temperature-melted fluororesin particle of the present invention is a particle containing high-temperature-melted fluororesin having an average particle diameter of 10 to 200 μm.
[0033] The second high-temperature-melt fluororesin particles can be manufactured from the resin used in the aforementioned first high-temperature-melt fluororesin particles. The second high-temperature-melt fluororesin particles differ from the aforementioned first high-temperature-melt fluororesin particles in that they do not contain fillers. Among the high-temperature-melt fluororesins, perfluororesins such as PFA and FEP, tetrafluoroethylene, hexafluoropropylene, and perfluoro(alkyl vinyl ether) copolymers are particularly preferably used in terms of the non-stick properties and heat resistance of the coating film. Among these, PFA is preferred in terms of heat resistance.
[0034] The average particle diameter of the second high-temperature-melted fluororesin particles is preferably in the range of 15 to 150 μm, more preferably 20 to 100 μm, and particularly preferably 25 to 70 μm. The average particle diameter of the second high-temperature-melted fluororesin particles must be larger than the average particle diameter of the first high-temperature-melted fluororesin particles. Commercially available high-temperature-melted fluororesin powder coatings may be used as the second high-temperature-melted fluororesin particles. The particles do not contain fillers, but may contain a small amount of additives, such as defoaming agents, on the outside of the particles (in the powder-mixed state).
[0035] (3) Charge modifier particles
[0036] Various types of conductive particles may be used as charge modifier particles of the present invention. Examples include metal powders, carbon fibers, carbon black, graphite, carbon nanotubes (CNT), and other carbon materials having a graphene structure, metal oxides (zinc oxide, tin oxide, titanium oxide, indium oxide, etc.), titanium carbide, titanium nitride, etc. Among these, carbon materials having a graphene structure are preferably used, and graphite is particularly preferably used. The function of the charge modifier particles is to be to attach to and coat the particles when the electrostatic properties differ between the first high-temperature-melt fluororesin particles containing a filler and the second high-temperature-melt fluororesin particles not containing a filler, thereby homogenizing the electrostatic properties of the surfaces and providing a uniform mixture without aggregation and separation when the particles are mixed together. In this specification, graphite is preferred because dry mixing is performed at high speed, and brittle graphite is pulverized to form fine sheets, which can be attached to and coated on the particles.
[0037] (4) Optional ingredients
[0038] The powder coating composition of the present invention may also contain additives of organic / inorganic materials as optional components within a range that does not affect the physical properties of the powder coating composition. Examples include polyarylene sulfide, polyether ether ketone, polyamide, polyimide, and other engineering plastics, metal powder, metal oxide (aluminum oxide, zinc oxide, tin oxide, titanium oxide, etc.), glass, ceramic, silicon carbide, silicon oxide, calcium fluoride, carbon black, graphite, mica, barium sulfate, etc. Additives having various shapes, such as fillers in the form of particles, fibers, or flakes, may be used as the shape of the additive. The amount is preferably 10 weight% or less and more preferably 5 weight% or less based on the total amount of the powder coating composition.
[0039] (5) Powder paint composition of the present invention
[0040] The powder coating composition of the present invention is characterized by containing 7 to 15 weight percent of filler material based on the total amount of the composition. The amount of filler in the powder coating composition of the present invention is preferably 9 to 14 weight percent, more preferably 11 to 13 weight percent, based on the total amount of the composition. The amount of filler in the above range enables a combination of high electrical conductivity and surface smoothness. In the prior art, it is difficult to evenly mix a large amount of filler material, and a smooth and uniform coating film cannot be obtained. In contrast, the powder paint composition of the present invention uses first high-temperature-melt fluororesin particles in which the filler is dispersed within the particles and is mixed with two types of second high-temperature-melt fluororesin particles to obtain a paint film having excellent uniformity, even though the entire composition contains a large amount of filler. Furthermore, by using a first high-temperature-melted fluororesin particle in which a filler is dispersed within the particle, the shear force can be reduced when mixing the first high-temperature-melted fluororesin particle, the second high-temperature-melted fluororesin particle, and the charge modifier particle, thereby enabling simple and efficient manufacturing of the composition.
[0041] The first high-temperature-melted fluororesin particles and the second high-temperature-melted fluororesin particles are blended such that the ratio of the amount of filler is within the above range. Preferably, the ratio of the first high-temperature-melted fluororesin particles to the second high-temperature-melted fluororesin particles is 40 to 70:30 to 60 weight%, more preferably 45 to 60:40 to 55 weight%, and even more preferably 60:40 weight%. Furthermore, the amount of charge modifier particles is preferably 0.01 to 5 weight%, more preferably 0.1 to 3.0 weight%, and even more preferably 0.2 to 2.0 weight% with respect to the total powder coating composition.
[0042] (6) Manufacturing method
[0043] A method for preparing the powder coating composition of the present invention is described below. The powder coating composition of the present invention is obtained by mixing a first high-temperature-melt fluororesin particle, a second high-temperature-melt fluororesin particle, and a charge modifier particle. Examples of mixing methods that can be used include a method of mixing particles in a dry state (dry blending / dry mixing) and a fluid mixing method using a Turbula mixer, etc., which stirs by rotating the mixing vessel itself. Examples of devices used for dry blending include, but are not limited to, cutter mixers, Henschel mixers, V-blenders with choppers, double-cone mixers with choppers, and rocking mixers. Since the powder coating composition of the present invention contains a larger amount of filler material than in the prior art, the effect of the filler material can be fully exerted without applying strong shear force.
[0044] (7) Coating film produced by the powder coating composition of the present invention
[0045] The "coating film" of the present invention is a coating film obtained by coating the powder coating composition of the present invention. To adhere to a substrate, a primer layer containing a fluororesin is preferably provided and attached to the substrate. The method of coating the powder coating composition of the present invention may be any commonly known powder coating method, but electrostatic powder coating is preferred. After coating, a coating film free of pinholes and other defects is obtained by heating to a temperature exceeding the melting point of the high-temperature molten fluororesin. The powder coating composition of the present invention is preferably used in cooking utensils, such as frying pans and rice cookers; heat-resistant release trays in factory lines (e.g., baking processes); products related to office equipment, such as fixing rollers, belts, inkjet nozzles, etc.; products related to industrial equipment in chemical plants, such as piping, etc.; and other products requiring non-stick properties and water and oil repellency.
[0046] Examples
[0047] The present invention will be described in more detail below based on examples and comparative examples. However, the present invention is not limited to these examples.
[0048] <Manufacture of Aluminum Test Specimens>
[0049] (A) Substrate surface treatment (shot blasting)
[0050] The surface of an aluminum substrate (JIS A1050 compliant product, 95 mm x 150 mm, 1 mm thick) was degreased using isopropyl alcohol, and then the surface was roughened by shot blasting using #60 alumina (Showa Blaster manufactured by Resonac Co., Ltd.) using a sandblaster (Pneuma-blaster SGF-4(A)S-E566 manufactured by Fuji Manufacturing Co., Ltd.).
[0051] (B) Undercoating (application of primer)
[0052] On the substrate processed in (A) described above, a liquid primer coating (fluororesin Teflon (Teflon) coating manufactured by Chemours-Mitsui Fluoroproducts Co., Ltd., water-based primer PJ-BN910) was sprayed and coated using an air spray coating gun (W-88-10E2 φ1 mm nozzle manufactured by Anest Iwata Corporation (manual gun)) at an air pressure of 3 to 4 kgf / cm^2. The coating was performed such that the weight of the coated liquid was approximately 0.9 to 1.4 g per sheet of substrate, and then drying was performed in a forced draft circulation furnace at 120°C for 15 minutes to form a coating film having a film thickness of 8 to 12 μm. The coating environment was a temperature of 25°C and a humidity of 60% RH.
[0053] Evaluation Method
[0054] (1) Thick coating
[0055] Using an electrostatic powder coating machine (Hand Gun System GX7500CS manufactured by Nihon Parkerizing Co., Ltd.), the aluminum substrates processed in (A) and (B) above were placed in a vertical and grounded state. Subsequently, the powder was electrostatically coated from a distance of approximately 25 cm at a coating voltage of 20 to 40 kV (negative) and an emission rate of approximately 50 g / min until no powder adhered. The coating environment was a temperature of 25°C and a humidity of 60% RH. The coated aluminum substrates were baked in a forced-air circulation furnace at 380°C for 30 minutes to form a coating film. The coating amount, the presence or absence of falling powder, the presence or absence of electrostatic repulsion, and the appearance of the obtained coating film were checked. A coating film with a coating weight of 2.8 g (corresponding to a film thickness of 100 μm) or more, no falling powder, and no electrostatic repulsion, foaming, or other defects was considered acceptable (○).
[0056] (2) Surface smoothness
[0057] Using an electrostatic powder coating machine (Hand Gun System GX7500CS manufactured by Nihon Parkerizing Co., Ltd.), the aluminum substrate processed in (A) and (B) above was placed horizontally in a grounded state, and the powder was electrostatically coated with a coating amount of approximately 2.8 g (corresponding to a film thickness of 100 μm) from a distance of approximately 25 cm at a coating voltage of 20 to 40 kV (negative) and an emission rate of approximately 50 g / min, and then baked at a specified temperature for 30 minutes. This was repeated 5 times (380°C for the first time and 360°C for the second and subsequent times) to obtain a coated material with a film thickness of 500 μm or more.
[0058] Surface roughness (Ra) was measured using the generated coated material. Surface roughness was measured using the touch needle method according to JIS B0601 with an evaluation length of 4 mm and a cutoff value of 0.8 mm using a HANDYSURF E-45A manufactured by Tokyo Seimitsu. Surface roughness of less than 2.0 μm was considered acceptable (○).
[0059] (3) Conductivity (300 μm)
[0060] Electrostatic coating was performed on a horizontally installed glass substrate (float glass, 95 mm x 150 mm, 2 mm thickness) using an electrostatic powder coater (Hand Gun System GX7500CS manufactured by Nihon Parkerizing Company Limited) such that the film thickness was 100 to 120 μm in each pass. Baking was performed for 30 minutes at a specified temperature and repeated three times (380°C for the first pass, and 360°C for the second and subsequent passes). After baking, the coated film was peeled in boiling water to obtain the film. Surface resistance values were measured using a Hiresta UX manufactured by Nitto Seiko Analytech Co., Ltd. with a UA probe at an applied voltage of 100 V. When the surface resistance was 10 7 If Ω is less than, the product passed the test (○).
[0061] (4) Conductivity (500 μm)
[0062] For the powder coating composition evaluated as acceptable (○) in (3), the surface resistance was measured in the same way for a 500 μm thick coating film. The surface resistance was 10 9 If Ω is less than, the product passed the test (○).
[0063] (5) Corrosion resistance
[0064] Corrosion resistance refers to the characteristic of a product to withstand specific conditions. For the coating composition of the present invention, the resistance of the coating composition to an aqueous hydrochloric acid solution after electrostatic painting was used as an evaluation index. The corrosion resistance of the product was considered improved if it bonded well to the coated substrate and formed a uniform and consistent thickness. Specifically, using an electrostatic powder coating machine (Hand Gun System GX7500CS manufactured by Nihon Parkerizing Company Limited), an aluminum substrate treated with the above (A) and (B) (except that (B) used a 65:35 mixture of EJ-CL107 and SG-CL600 (both products of Chemours-Mitsui Fluoroproducts) instead of PJ-BN910) was placed horizontally in a grounded state and electrostatically coated with powder at a distance of approximately 25 cm with a coating amount of approximately 2.8 g (corresponding to a film thickness of 100 μm) at a coating voltage of 20 to 40 kV (negative) and an emission rate of approximately 50 g / min, and then baked at a specified temperature for 30 minutes. This was repeated three times (380°C for the first time and 360°C for the second and subsequent times) to obtain a coated material with a film thickness of 300 μm or more.
[0065] Using a Yamazaki type lining tester (LA-15, manufactured by Yamazaki Seiki Laboratory), a 5% aqueous hydrochloric acid solution (95°C) was applied to the coated surface of the resulting coating. The surface of the coating was visually observed every 24 hours, and the time until blistering occurred was compared.
[0066] Ingredients
[0067] ㆍ Graphite A: SGP-5 manufactured by SEC Carbon Co.
[0068] ㆍ Graphite B: UF-G5 manufactured by Resonac Corporation
[0069] PFA aqueous dispersion
[0070] A dispersion of a tetrafluoroethylene / perfluoropropyl vinyl ether (TFE / PPVE) copolymer was prepared by the method according to Examples 1 to 3 described in Japanese Patent Publication No. 5588679. (MFR of solid resin = 16.6 [g / 10 min], average particle diameter: 0.186 μm, comonomer (PPVE) ratio: 3.3 wt%, PFA content in dispersion: 30.6 wt%)
[0071] ㆍ PFA Powder Coating: Fluoropolymer Teflon (Trademark) coated powder topcoat MJ-508 manufactured by Chemours-Mitsui Fluoroproducts Company Limited, average particle diameter d50: approximately 50 μm
[0072] ㆍ Perfluoroheptene (Chemours-Mitsui Fluoroproducts Company Limited, Opteon (registered trademark) SF10)
[0073] ㆍ 60% aqueous nitric acid solution (manufactured by FUJIFILM Wako Pure Chemical Corporation)
[0074] (Manufacturing Example)
[0075] (Preparation of the first high-temperature-molten fluororesin particle 1)
[0076] 246.5 g of pure water was added to a 2 L stainless steel beaker, and 41.2 g of graphite A was added. Then, ultrasonic dispersion treatment was performed for 5 minutes using an ultrasonic generator (UE-1002288-8A ultrasonic generator manufactured by Ultrasonic Engineering Co., Ltd.). The resulting dispersion solution was further added to a stainless steel container containing 522 g of PFA aqueous dispersion, and stirred at 600 rpm for 5 minutes using a downflow type propeller type 4-blade stirrer. Subsequently, 11.6 g of a 60% aqueous nitric acid solution was added, and after confirming a rapid increase in viscosity, 132.1 g of perfluoroheptene was added to generate coarse aggregate particles in the liquid. The coarse aggregate particles removed by filtration were washed three times with pure water. After washing, the sample was placed on a tray and dried at 120°C for 1 hour and at 290°C for 3 hours to obtain the first high-temperature-melted fluororesin particle 1. The average particle diameter of the obtained particle was d50: 31.0 μm. The amount of graphite in the obtained high-temperature-melted fluororesin particle 1 was calculated to be 20 wt% based on the weight change during heating at 600°C for 30 minutes in a nitrogen environment using a tubular electric furnace TMF-300N (manufactured by As One Corp.).
[0077] (Example 1)
[0078] In a small Henschel mixer (FM10B manufactured by Nippon Coke & Engineering Co., Ltd.), 1200 g of the first high-temperature-melt fluororesin particles 1 prepared in the above preparation example, 782 g of PFA powder coating (MJ-508 manufactured by Chemours-Mitsui Fluoroproducts Company Limited, average particle diameter d50: 51.2 μm) as the second high-temperature-melt fluororesin particles, and 18 g of graphite B as a charge modifier were added, the powder coating composition was mixed, and stirred at 1000 rpm for 10 minutes. The ratio of the filler to the total powder coating composition was adjusted to 12.0 wt%.
[0079] (Example 2)
[0080] A powder coating composition was obtained in a manner similar to that of Example 1 described above, except that 1,100 g of the first high-temperature-melted fluororesin particle 1 and 882 g of PFA powder coating were used. The ratio of the filler to the total powder coating composition was adjusted to 11.0 wt%.
[0081] (Example 3)
[0082] A powder coating composition was obtained in a manner similar to that of Example 1 described above, except that 1000 g of the first high-temperature-melted fluororesin particle 1 and 982 g of PFA powder coating were used. The ratio of the filler to the total powder coating composition was adjusted to 10.0 wt%.
[0083] (Example 4)
[0084] A powder coating composition was obtained in a manner similar to that of Example 1 described above, except that 900 g of the first high-temperature-melted fluororesin particle 1 and 1082 g of PFA powder coating were used. The ratio of the filler to the total powder coating composition was adjusted to 9.0 wt%.
[0085] (Example 5)
[0086] A powder coating composition was obtained in a manner similar to that of Example 1 described above, except that 800 g of the first high-temperature-melted fluororesin particle 1 and 1182 g of PFA powder coating were used. The ratio of the filler to the total powder coating composition was adjusted to 8.0 wt%.
[0087] (Preparation of the first high-temperature-melted fluororesin particle 2)
[0088] In the above preparation example, a first high-temperature-melted fluororesin particle 2 was obtained using 171.0 g of pure water, 22.5 g of graphite A, 597.4 g of PFA aqueous dispersion, 12.8 g of 60% nitric acid solution, and 146.2 g of perfluoroheptene. The amount of graphite in the high-temperature-melted fluororesin particle 2 was adjusted to 11 wt%.
[0089] (Comparative Example 1)
[0090] A powder coating composition was obtained in a manner similar to that of Example 1 described above, except that 950 g of first high-temperature-melted fluororesin particles 2, 1000 g of PFA powder coating, and 50 g of graphite B were used instead of first high-temperature-melted fluororesin particles 1. The ratio of filler to the total powder coating composition was adjusted to 5.2 wt%.
[0091] (Comparative Example 2)
[0092] A powder coating composition was obtained in a manner similar to that of Example 1 described above, except that 400 g of the first high-temperature-melted fluororesin particle 1 and 1582 g of PFA powder coating were used. The ratio of the filler to the total powder coating composition was adjusted to 4.0 wt%.
[0093] (Comparative Example 3)
[0094] A powder coating containing only the first high-temperature-melted fluororesin particle 1 was used as Comparative Example 3. The ratio of the filler to the total powder coating was adjusted to 20.0 wt%.
[0095] (Comparative Example 4)
[0096] 1880 g of PFA powder coating and 120 g of graphite A were added to a small Henschel mixer (FM10B manufactured by Nippon Koch & Engineering Company Limited), the powder coating composition was mixed, and the mixture was stirred at 1000 rpm for 10 minutes to obtain a powder coating composition. The ratio of filler to the total powder coating composition was adjusted to 6.0 wt%.
[0097] The compositions of the examples and comparative examples are summarized in Table 1. Furthermore, the results of evaluation methods (1) to (5) are summarized in Table 2.
[0098] [Table 1]
[0099]
[0100] [Table 2]
[0101]
[0102] In Examples 1 to 5, when 8 to 12 weight percent of filler was included in the final composition, the composition not only exhibited good thick coating properties, surface smoothness, and conductivity (300 μm and 500 μm), but also showed significantly improved corrosion resistance compared to Comparative Example 1, which included 5.2 weight percent of filler in the final composition. This improvement in corrosion resistance can be attributed to the fact that the composition of the examples has a relatively large amount of filler uniformly dispersed within the composition, and thus a good coating film was formed by electrostatic coating.
[0103] In Comparative Examples 1, 2, and 4, which have low filler content, the surface resistance is 10 when evaluating conductivity (300 μm). 7 It was greater than Ω and therefore did not exhibit sufficient conductivity, so the conductivity (500 μm) was not evaluated. On the other hand, Comparative Example 3, containing 20 wt% of filler, had good conductivity, but the thickness coating and surface smoothness were insufficient.
[0104] The present invention is not limited to the embodiments described in this specification or the contents of the embodiments of the invention disclosed in this specification, and includes the contents of the invention appropriately modified based on the details disclosed in this specification, as long as such modifications do not contradict the spirit of the invention. Industrial applicability
[0105] By applying the high-temperature molten fluororesin powder coating composition of the present invention thickly by an electrostatic powder coating process, a coating film having excellent surface smoothness, high corrosion resistance, and excellent electrical conductivity can be obtained.
Claims
Claim 1 A powder coating composition comprising a powder mixture, wherein the powder coating composition comprises: first high-temperature-melted fluororesin particles in which a filler is dispersed; second high-temperature-melted fluororesin particles having an average particle diameter of 10 to 200 μm; and charge modifier particles, wherein the amount of the filler is 7 to 15 weight% based on the total amount of the powder mixture. Claim 2 A powder coating composition according to claim 1, wherein the ratio of the first high-temperature-melted fluororesin particles to the second high-temperature-melted fluororesin particles is 40 to 70:30 to 60 weight%, and the amount of charge adjusting agent particles is 0.01 to 5 weight% based on the total amount of the powder coating composition. Claim 3 A powder coating composition according to claim 1 or 2, wherein the filler is a carbon material having a graphene structure. Claim 4 A powder coating composition according to claim 1 or 2, wherein the charge modifier particles are made of graphite. Claim 5 A powder coating composition according to claim 1 or 2, wherein the high-temperature-melted fluororesin is a perfluororesin. Claim 6 A coating film having a thickness of 100 μm or more, comprising a powder coating composition according to claim 1 or 2. Claim 7 Article comprising a coating film according to paragraph 6.